"A Question of Freedom": Black Workers, Union Membership, and Political Participation. (December 2022) - Wilkerson, Tiamba M.
Despite the historic connection between labor and citizenship rights for Black people, the specific role of labor organizations in mobilizing Black workers remains understudied. This research examines the effect of union membership on Black political and civic engagement. Analyzing survey data from 1973 to 1994, results show Black union members were significantly more likely than Black nonunion workers to participate in a range of political activities, and to greater degrees, especially members with less education. Understanding unions as important sites of political activism for Black workers is critical for the growth and maintenance of both the labor movement and the Black freedom struggle.